CODE SWITCHING IN SOCIAL MEDIA TWITTER - Riris Desnia Sihombing; Meisuri Meisuri (LINGUISTICA, 2014)
ABSTRACT The study deals with the types of code switching and reasons why people switch their language in social media Twitter. The objectives of study are to find out contextual type and the grammatical type of code-switching which is mostly used in social media Twitter and to explain audience’s reasons switch the code in social media Twitter. The research conducted by using descriptive qualitative design. The primary data collected by tweets from the timelines of Twitter users, the secondary data were the questionnaires to collect information about audiences’s reason switch the code on Twitter. The result showed that the dominant type of grammatical types that used by the  user is Inter sentential code switching, then it is followed by tag code switching type and intra sentential code switching. The dominant type of contextual types that used by the user is metaphorical code switching and it is followed by situational code switching. There are eight reasons why people switch the code in the social media Twitter, the most common reasons for people switch the languange is due to the lack of equivalent lexicon in the languanges. It is because of real lexical need. Keyword : twitter, social media, code switching